Evaluation of CHIRPS and CFSR precipitation products over the Mujib Basin, Jordan - Alsalal, Suheir; Tan, Mou Leong; Narimah Samat,; AL-Bakri, Jawad T.; Li, Longhui (Penerbit Universiti Kebangsaan Malaysia, 2023)
Open-source climate products provide the possibility of complementing observed data, which sometimes suffer from the scarcity and inconsistency issues. This study aims to evaluate the accuracy of two open-source climate products, Climate Hazards Group Infrared Precipitation with Station (CHIRPS 0.05) and Climate Forecast System Reanalysis (CFSR), in capturing precipitation over the Mujib Basin, Jordan, from 2002 to 2012. Both products were compared with observed data collected from ten climate stations using the point-to-pixel comparison approach at the daily, monthly, seasonal, and annual scales. The coefficient of determination (R2 ), the root mean square error (RMSE), the mean absolute error (MAE), and the relative bias (RB) were used to evaluate the efficiency of CHIRPS and CFSR. While, categorical statistics such as the probability of detection (POD), false alarm ratio (FAR), critical success index (CSI), Heidke skill score (HSS), and frequency bias index (FBI), were used to analyze the precipitation detection capability. Results indicated good correlations between open-source climate products and observed data in the monthly time period, where the R 2 values ranged from 0.65 (CFSR) to 0.76 (CHIRPS). Besides that, CHIRPS performed better than CFSR for the daily, monthly, and seasonal time steps, with a better ability in detecting precipitation. Therefore, CHIRPS is recommended to fill the missing gaps of observed data and to detect the drought conditions over the Mujid Basin.